Strindberg's dramaturgy - Stockenström, Göran (Nordic series ;, 1988)
The contributors to ""Strindberg's Dramaturgy""--An international group of scholars, critics and directors - explore this complex pattern of signification or meaning in both his dramatic discourse and the actual staging of the plays. Their aim is to better understand Strindberg's impact on 20th century theatre from this dual point; the dialetic tension between text and stage characterizes every chapter in the book. Structured in four parts, the book opens with several essays that establish for Strindberg a historical context reaching beyond theatre - his place in Western humanism, his relatio